Abstracionismo informal em São Paulo: a obra de Zita Viana de Barros - Lacerda, Mariana Duarte Garcia de [UNIFESP] (2016)
This research aimed to study the manifestations of informal abstraction in São Paulo and the discussions on abstract art starting from the printings of Zita Viana de Barros, made between the years 1960 and 1970, identifying, cataloguing and analysing its work and contextualizing such production in light of the national artistic scene. The research led to a retrospective on the Brazilian Art History in the 1950s and 1960s, rethinking its categories due to Brazilian typical independence, especially through questioning the abstractionism, from a point of view that differs from the defence of constructive abstract art, which have been the keynote of art criticism and the history studies in Brazil. Imagery interpretation of the works related in this study were made through the philosophical and methodological framework designed by Charles Peirce, in which the aesthetic provides the basis for ethics, which in turn provides the basis for semiotics, in an evolutionary relationship of dependency. Informal Abstraction as the result of the combination of Zen?s philosophy indirect speech with the occidental liberty. With this mixture it instituted the notion of consciousness in intuition and sensibility in the occidental perspective that divided everything between rationality and unconsciousness.